2007
DOI: 10.1007/s11103-007-9227-y
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis thaliana deficient in two chloroplast ascorbate peroxidases shows accelerated light-induced necrosis when levels of cellular ascorbate are low

Abstract: Arabidopsis chloroplasts have a multi-layered defense against hydrogen peroxide (H(2)O(2)) that includes a stromal and thylakoid ascorbate peroxidase (sAPX and tAPX). Single and double null mutants in SAPX and TAPX (sapx and tapx) were each crossed with ascorbate deficient vtc2. The single, double and triple mutants did not show visual light stress phenotypes when grown at control or high light intensities (CL and HL; 120 and 1,000 micromol photons m(-2) s(-1)). Upon shift from CL to HL, mesophyll of expanded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(85 citation statements)
references
References 64 publications
6
79
0
Order By: Relevance
“…The trend of the changes in the MDA content was similar to that of Φ NF indicating the involvement of ROS both in the development of membrane damage and in PSII inactivation. According to Giacomelli et al [47], APX and SOD isoforms are of importance in the elimination of ROS in chloroplasts. The rise in the activity of APX was observed in parallel to the decline of lipid peroxidation and the increase of Φ PSII .…”
Section: Antioxidative Defencementioning
confidence: 99%
“…The trend of the changes in the MDA content was similar to that of Φ NF indicating the involvement of ROS both in the development of membrane damage and in PSII inactivation. According to Giacomelli et al [47], APX and SOD isoforms are of importance in the elimination of ROS in chloroplasts. The rise in the activity of APX was observed in parallel to the decline of lipid peroxidation and the increase of Φ PSII .…”
Section: Antioxidative Defencementioning
confidence: 99%
“…1B-1D), we hypothesized that DREB2C may regulate oxidative stress-inducible antioxidant genes. Among antioxidants, APXs play a pivotal role in removing reactive oxygen species by catalyzing the conversion of highly damaging H 2 O 2 into H 2 O (Giacomelli et al, 2007). Hence, we assessed the expression of nine Arabidopsis APX isoforms (Mittler et al, 2004) in DREB2C overexpressors by RT-PCR.…”
Section: Apx Genes Were Induced In Dreb2c Overexpressorsmentioning
confidence: 99%
“…These reports strengthen the link between ROS scavenging and metabolism and demonstrate that proper regulation of ROS requires reducing power that can be supplied by photosynthesis, respiration, and/or different carbon utilization pathways. Insight into the cross talk between different ROS and ROS scavenging mechanisms was gained from studies of double or triple mutants that lack key ROS scavenging enzymes in different subcellular locations (Giacomelli et al, 2007;Miller et al, 2007) and exploration of cross talk between distinct ROS such as singlet oxygen and H 2 O 2 (Laloi et al, 2007). These studies not only exposed redundancy of the ROS scavenging network but also suggested that different antioxidant enzymes and different ROS in the same or different compartments mediate signature signals that control chloroplast function and plant response to various environmental stimuli.…”
Section: New Perspectives On Ros Scavengingmentioning
confidence: 99%